Computer-aided design and synthesis of 3-carbonyl-5-phenyl-1H-pyrazole as highly selective and potent BRAFV600E and CRAF inhibitor. (1st January 2019) - Kim, Jinwoong; Choi, Byeongha; Im, Daseul; Jung, Hoyong; Moon, Hyungwoo; Aman, Waqar; Hah, Jung-Mi
Abstract: BRAF belongs to the upstream portion of the MAPK pathway, which is involved in cell proliferation and survival. When mutations occur in BRAF, downstream MEK and ERK are phosphorylated irrespective of RAS, resulting in melanoma-like cancer. Over the years, small molecules targeting BRAFV600E have been discovered to be very effective melanoma drugs, but they are known to cause the BRAF paradox. Recently, it was shown that this paradox is caused by the heterodimer phenomenon of BRAF/CRAF. Here, we suggest one method by which paradoxical activation can be avoided by selectively inhibiting BRAFV600E and CRAF but not wild-type BRAF. From previous report of N -(3-(3-alkyl-1 H -pyrazol-5-yl) phenyl) aryl amide as a selective inhibitor of BRAFV600E and CRAF, we present compounds that offer enhanced selectivity and efficacy with the aid of molecular modelling.